Scandium and Boron co-alloyed AlN thin films with improved piezoelectric and ferroelectric properties - Wu, Cheng Lung (Nanyang Technological University, 2024)
This study explores the optimization of piezoelectric and ferroelectric properties of doped aluminum nitride (AlN) films, specifically investigating the effects of scandium (Sc) and boron (B) doping. The experimental setup involves depositing a Metal-Ferroelectric-Metal (MFM) thin film stack on 200mm silicon wafers and characterizing the samples using various techniques such as scanning electron microscopy (SEM) for morphology analysis, X-ray diffraction (XRD) for crystal orientation measurement, piezotest for piezoresponse measurement, and electrical testing for ferroelectric switching field assessment.